Pertumbuhan dan Hasil Kedelai (Glicine max (L) Merr) Akibat Tinggi Muka Air Tanah pada Beberapa Stadia Pertumbuhan - Lenny M. Mooy; Theresia Ginting (Partner, 2012)
The Growth and the Yield of Soy (Glycine max (L) Merr) Due to the Height of Water Soil Surface on Some Growing Stadia Soy is a kind of nut plants that has important role for food consumption in the world. Water – logged cultivation is a kind of technology used to improve the growth as well as to increase the yield of soy varieties where much water is available. This study is aimed at finding out the effect of interaction between the height of water level and the growing stadia on the growth and the yield of soy. The study has been done in Oebelo Village of Kupang Tengah Sub District of East Nusa Tenggara Province, started in April and ended in October 2010. This Study employed Group Randomized Design (GRD) with factorial pattern of three (3) repetitions. The first factor tried out in this study is the treatment of surface water soil height that consists of 25 cm (T1); 20 cm (T2); and 15 cm (T3).  The result showed that growing stadia consists of active vegetative (T2S1) makes the plant grow higher (55,40 cm); the leaves become   wider (56,67 cm²); the number of filled – stem increases (74,33); the plants nuts weight becomes 42,27 g  and the plants weight is 76,80 g, all of which are higher than of the treatments. It is suggested that the cultivation of soy plant should be done by means of watering down the active vegetative with the height of water level being 10 cm. Key words: Soy, the height water soil surface, growing stadia.